1984
DOI: 10.1093/bja/56.10.1101
|View full text |Cite
|
Sign up to set email alerts
|

Early Extubation of the Trachea After Open Heart Surgery for Congenital Heart Disease

Abstract: The results of early extubation after open heart surgery for congenital heart disease in 209 consecutive patients have been reviewed. No patient younger than 3 months of age, 52% of those between 3 and 12 months, and 88% of those older than 12 months had the tracheal tube removed in the operating theatre. Four patients required reintubation of the trachea, three because of respiratory difficulty and one because of cerebral oedema. There were two deaths in the extubated group. Twelve patients had PaO2 values le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 10 publications
2
33
0
2
Order By: Relevance
“…Study of the Neirotti et al (15) showed, as well as our research, that failure to thrive is one of the risk factor of prolonged ventilation [95%CI (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)]. …”
supporting
confidence: 71%
“…Study of the Neirotti et al (15) showed, as well as our research, that failure to thrive is one of the risk factor of prolonged ventilation [95%CI (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)]. …”
supporting
confidence: 71%
“…Although the cardiovascular status of our patients was such that a pure inhalational technique could have been used, intraoperative fentanyl was administered in all cases, although the total dosages were less for the patients who were extubated in comparison with those for the group who remained intubated (Table II). Similarly, Schuller et al 4 found that, in more criticaily ill patients, administering small doses of fentanyl (10 i.Lg.kg -I) reduced the need for an inhalational agent, provided greater cardiac stability, and did not complicate extubation of the trachea at the end of the procedure.…”
Section: Discussionmentioning
confidence: 95%
“…Immunological mechanisms and anatomical characteristics are relatively different in children from those in adults (11,12). Prolonged mechanical ventilation following pediatric cardiac surgery was consistently associated with longer CPB time in other studies (13,14). Increased CPB time is required for more complex cases or if unexpected difficulties occur.…”
Section: Discussionmentioning
confidence: 93%